(untitled) (Advances in Applied Mathematics and Mechanics, 2014)
In this paper, we study wave interaction with an emerged porous media. The governing equation is shallow water equations with a friction term of the linearized Dupuit-Forcheimer's formula. From the continuity of surface and horizontal flux, we derived the wave reflection and transmission coefficient formulas. They are similar to the corresponding formulas of the submerged solid bar breakwater. We solve the equations numerically using finite volume method on a staggered grid. The numerical wave reduction in the porous media confirms the analytical wave transmission curve.